Dramatic play in the development of body expression in early education - Cruz Vera, Nancy de la; Bonilla Jurado, Diego; Lucio Quintana, Araceli (Revista Universidad de Guayaquil, 2018)
The dramatic play constitutes an educational space and tool that allows to develop the school curriculum in other areas, as is the body expression. In addition, it is shown as a powerful tool for the development of social skills and education in values, for its strong interpersonal and relational character. In this work, we intend, first of all, to try to clarify the terminology around the use of dramatization in education. In a second moment, the group of contributions of the dramatization to the school curriculum is described, in particular in the stage of primary education, in which the authors have developed most of their research. The methodology that goes with the study is that of Montessori which seeks that the boy and girl can bring to light their potential. It is also intended to give a current, critical and detailed vision of the corporal expression, since this information is basic and fundamental to be able to carry out the corporal expression in the different educational scenarios of the primary education.